Mutual funds performance: an analysis of mutual funds’ return (IDLC AML) compared to the Market Return (DSEX) - Biva, Basharat (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.